Pengaruh Islamic Banking Service Quality dan Brand Islam terhadap Loyalitas Nasabah Bank Syariah di Indonesia - Auliana; Sissah; Sri Rahmah; Nurfitri Marthaliah (Jurnal Ekonomi Islam, 2023)
The purpose of this study is to explain analyzing the influence of Islamic Banking Service Quality and Islamic Brand on customer loyalty at Bank Syariah Indonesia KCP Sarolangun. The type of research used in this research is quantitative research with a descriptive approach. The sample was used by Proportional Stratified Random Sampling.   Methods   of   data   collection   using   observation,   questionnaires,   and documents. Data analysis method using Multiple Regression Analysis. The results show that Islamic Banking Service Quality and Islamic Brand have a simultaneous effect on customer  loyalty  of  Bank  Syariah  Indonesia  KCP  Sarolangun.  Partially,  Islamic Banking Service Quality and Islamic Brand also simultaneously affect customer loyalty of Bank Syariah Indonesia KCP Sarolangun. Adjusted R Value Square of 0.208 = 20.8% means that the independent variable jointly affects the dependent variable by 20.8% and the rest is influenced by other variables not included in the study.